Gd (III) DOTA‐Functionalized Phthalocyanine Nanodots for Magnetic Resonance Imaging and Photothermal/Photodynamic Therapy. Issue 19 (13th August 2020) - Wu, Fengshou; Chen, Jingwen; Li, Haolan; Li, Cheng; Wang, Han; Liu, Genyan; Luo, Xiaogang; Zhu, Xunjin
Abstract: The development of organic nanoagents that integrate diagnosis and therapy has gained considerable attention over the last decades. Here, phthalocyanine‐based nanodots (ZnPc‐NDs) are developed through a facile hydrothermal method. The self‐aggregation of molecules in nanostructures facilitates the fluorescence quenching and nonradiative heat generation. Accordingly, ZnPc‐NDs display the photodynamic and photothermal effect simultaneously upon near‐infrared laser irradiation. To endow ZnPc‐NDs with the diagnostic function, the surface of nanodots is functionalized with Gd(III) chelates to yield ZnPc‐Gd, providing the magnetic resonance performances. The biocompatibility and high photocytoxicity of ZnPc‐Gd toward HeLa cells are verified through the cell counting kit‐8 method. Due to the presence of paramagnetic metal, ZnPc‐Gd exhibits a distinct magnetic resonance signal in vitro and in vivo. Upon irradiation with a 808 nm laser, ZnPc‐Gd can efficiently inhibit the growth of tumors with minor side effects. Thus, the as‐prepared ZnPc‐Gd can be utilized as a promising nanoagent for magnetic resonance imaging‐guided cancer phototherapy. Abstract : Phthalocyanine‐based nanodots (ZnPc‐NDs) are developed through a facile hydrothermal method. ZnPc‐NDs displays photodynamic and photothermal effect simultaneously upon 808 nm laser irradiation. The surface of nanodots is then functionalized with Gd(III) chelates to yield ZnPc‐Gd, providing the magnetic resonance performances. The as‐prepared ZnPc‐Gd is demonstrated to be an efficient nanoagent for magnetic resonance imaging‐guided cancer phototherapy.